ZNF263–NuRD-mediated repression of STAT1 curtails MHC-I antigen presentation and IFN-γ efficacy in prostate cancer - Han Guan; Likai Mao; Fang Fang; Tiange Wu; Yifei Cheng; Zonghao You; Hao Lin; Ruixin Zhang; Junyong Zhuang; Gao-Jun Teng; Chuanjun Shu; Shenghong Ju; et al. (Proceedings of the National Academy of Sciences, 2026)
Loss of major histocompatibility complex (MHC)-I is a hallmark of prostate cancer (PCa) immune evasion and immunotherapy failure. Here, we identify ZNF263 as a transcriptional repressor that silences MHC-I by recruiting nucleosome-remodeling and deacetylase (NuRD) to the STAT1 promoter, reducing STAT1 and MHC-I expression. Hypoxia enhances this repression through two ZNF263 modifications: phosphorylation-driven phase separation that strengthens NuRD interaction and O-GlcNAcylation at S662 that aids STAT1 promoter binding. O-GlcNAcylation also promotes interaction with protein kinase, DNA‑activated catalytic subunit (PRKDC), amplifying phosphorylation. Interferon‑gamma (IFN‑γ)‑induced MHC-I induction is augmented upon ZNF263 loss. In silico docking identified Viroptic as a Krüppel‑associated box (KRAB) pocket binder disrupting ZNF263–NuRD, derepressing STAT1, and potentiating IFN-γ antitumor immunity in vivo. High ZNF263 correlates with low MHC-I, scarce CD8+ T cells, and poor survival, providing rationale for targeting ZNF263 in PCa immunotherapy.